2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33313
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Engagements with Reflection: Insights from Undergraduates

Abstract: Wendy is a second-year PhD student in Human Centered Design and Engineering at the University of Washington studying the development of equitable engineering education. Her work draws from the fields of engineering education, design, and learning sciences. Dr. Jennifer A. Turns, University of WashingtonJennifer Turns is a Professor in the Department of Human Centered Design & Engineering at the University of Washington. She is interested in all aspects of engineering education, including how to support enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In both studies, results did not show a significant difference between students' performance before and after engaging in EAR [8], or the performances of students who did and did not engage in EAR [9]. In the study by Roldan [10] undergraduate students were interviewed about how they understood and engaged in reflection. Results showed that students engaged in a variety of reflective strategies, both positive and negative, suggesting that students may be more likely to discuss reflection than previously thought.…”
Section: B Metacognition At the University Levelmentioning
confidence: 96%
“…In both studies, results did not show a significant difference between students' performance before and after engaging in EAR [8], or the performances of students who did and did not engage in EAR [9]. In the study by Roldan [10] undergraduate students were interviewed about how they understood and engaged in reflection. Results showed that students engaged in a variety of reflective strategies, both positive and negative, suggesting that students may be more likely to discuss reflection than previously thought.…”
Section: B Metacognition At the University Levelmentioning
confidence: 96%